Effect of Autologous Platelet Rich Fibrin (PRF) on Post-operative Complications and Healing Following the Extractions of Impacted Mandibular Wisdoms: An Open Label Randomized Controlled Trial - Jawed, Hamza; Zahid, Anita; Hasan, Syed Wajid; Anis, Mehak; Wazir, Hammad; Khursheed, Haziq (Journal of Neonatal Surgery, 2025)
Background: The extraction of impacted mandibular third molars is a commonly performed oral surgical procedure associated with various post-operative complications, including pain, swelling, and delayed soft tissue healing. Objective: This study aimed to evaluate the effect of PRF on post-operative complications and healing following the extraction of impacted mandibular third molars. Methods: A total of 134 participants with impacted mandibular third molars were randomly allocated into two groups: Group A (PRF treatment) and Group B (control, natural clot formation). Post-operative pain, swelling, and soft tissue healing were assessed on the 3rd and 7th post-operative days. Swelling was measured at two sites, and soft tissue healing was evaluated using Landry and Turnbull criteria. Results: The mean age of participants was 27 years in Group A and 26.2 years in Group B. Pain incidence was lower in Group A (10.4%) compared to Group B (20.8%), although the difference was not statistically significant (p > 0.05). Group A showed a significantly lower rate of swelling (68.5%) compared to Group B (100%) (p = 0.000). Soft tissue healing was significantly better in Group A, with 100% of patients exhibiting excellent healing compared to 80.5% in Group B (p = 0.0001). Conclusions: The application of PRF following impacted mandibular third molar extraction significantly reduces post-operative swelling and enhances soft tissue healing. While pain reduction was not statistically significant, the overall improvement in post-operative recovery suggests that PRF may be a beneficial adjunct in oral surgery to promote faster healing and reduce complications.